A case report of an asymptomatic male child with multiple entero-enteric fistulae post multiple magnet ingestion. (2019) - Taher, Heba; Azzam, Ahmed; Khowailed, Omneya; Elseoudi, Mohamed; Shaban, Muayad; Eltagy, Gamal
Highlights: Multiple magnet ingestion in children is challenging to diagnose if asymptomatic. Symptoms include vomiting, abdominal pain, discoloured stools or fever. Meticulous history, patient examination and investigations are necessary. Intestinal pressure necrosis and multiple fistulas can occur yet remain asymptomatic. Resection and anastomosis may be the sole management in such cases. Abstract: Introduction: Foreign body ingestion cases are very common in children. They usually present with obvious symptoms allowing proper diagnosis and management; however, magnet ingestion can be asymptomatic. This disorder is considered uncommon as well as challenging to diagnose before complications of intestinal obstruction or peritonitis occur due to entrapment of intestinal walls in the magnetic field. Case presentation: An asymptomatic four-year-old male child was admitted to our centre after passing two bullet-shaped magnets in stool that were noticed by his mother. The child was asymptomatic. An abdominal X-ray revealed five bullet-shaped magnets in the lower abdomen. Laboratory investigations were normal except for a mild leukocytosis. Surgery was performed with excision of seven entero-enteric fistulae and two intestinal anastomoses. Discussion: Between 2003 and 2006, the Centers for Disease Control and Prevention reported 20 complicated cases of magnet ingestion in children aged 10 months to 11 years among whom 75% had bowel perforations, and 20% suffered from generalized peritonitis. Half that number of patients required emergency laparotomy. As a result, the Consumer Product Safety Commission (CPSC) issued the first warning announcing the hazards of high-powered magnets used in children's toys, which had been increasing exponentially. It is clear that the diagnosis of magnet ingestion is made commonly due to complications, such as peritonitis or death. However, the patient in this case was completely asymptomatic and had no complications. Conclusion: A high index of suspicion regarding complications is recommended in asymptomatic cases of suspected magnet ingestion. Avoid delaying intervention once a diagnosis has been made.